Drowning related out-of-hospital cardiac arrests: Characteristics and outcomes - Dyson, K.; Morgans, A.; Bray, Janet; Matthews, B.; Smith, K. (2013)
Aim: There are few studies on drowning-related out-of-hospital cardiac arrest (OHCA) in which patients are followed from the scene through to hospital discharge. This study aims to describe this population and their outcomes in the state of Victoria (Australia). Methods: The Victorian Ambulance Cardiac Arrest Registry was searched for all cases of OHCA with a precipitating event of drowning attended by emergency medical services (EMS) between October 1999 and December 2011. Results: EMS attended 336 drowning-related OHCA during the study period. Cases frequently occurred in summer (45%) and the majority of patients were male (70%) and adult (77%). EMS resuscitation was attempted on 154 (46%) patients. Of these patients, 41 (27%) survived to hospital arrival and 12 (8%) survived to hospital discharge (5 adults [6%] and 7 [12%] children). Few patients were found in a shockable rhythm (6%), with the majority presenting in asystole (79%) or pulse-less electrical activity (13%). An initial shockable rhythm was found to positively predict survival (AOR 48.70, 95% CI: 3.80-624.86) while increased EMS response time (AOR 0.73, 95% CI: 0.54-0.98) and salt water drowning (AOR 0.69, 95% CI: 0.01-0.84) were found to negatively predict survival. Conclusions: Rates of survival in OHCA caused by drowning are comparable to other OHCA causes. Patients were more likely to survive if they did not drown in salt water, had a quick EMS response and they were found in a shockable rhythm. Prevention efforts and reducing EMS response time are likely to improve survival of drowning patients.